SISTEM INFORMASI GEOGRAFIS (SIG) UNTUK PEMANTAUAN ANEMIA IBU HAMIL (STUDI DI DINAS KESEHATAN KABUPATEN (DKK) BREBES) - Siti Nurhayati (Kesmas Indonesia, 2008)
A main task of Section of Founding Society’s Nutrient at the District Health Office of Brebes is to plan, to conduct, to develop a program of improving society’s nutrient and coping with nutrient problem. Anemia because of iron defeciency on the pregnancy woman is one of the nutrient problems in District of Brebes. The aim of research was to devolep an information system based on Geographical Information System (GIS) for monitoring anemia of pregnancy woman. This research had two steps. First step was a qualitative research that was used seven methodology steps of FAST development (Framework for the Application of System Techniques). Second step was a quantitave research using pre-exprmental one group posttest only/the one shot case study design. In this design, the treatment that had been done was measured and observed (pottest). Data of observation was analyzed by a descriptive method using a considered average. Subjects were the head of the district health office of Brebes, the head of sub-departement of the public health empowerment, the head of section, and the staffs of section of founding society’s nutrient. Information system has overall considered average equal to 4,05. It means that user generally has apporved it. The considered average for accessibility, completeness of information,relevancy, and speed is equal to 4, for ease is equal to 4,25, and for management of data basis is equal to 4,08. It means that accessibilty, completeness of information, revalancy, speed, ease, and management of data basis for an information system that has been devoleped, is approved by respondent and has a good value.